ECONOMIC ASSESSMENT OF THE INNOVATIVE DEVELOPMENT OF SPONGE FERROTUNGSTEN PRODACTION IN DOMESTIC METALLURGY - Skachkov, Viktor; Hrigoriev, Dmytro; Karpenko, Anna (Scientific Journal "Metallurgy", 2023)
The paper examines the production of a new alloying material based on tungsten by powder metallurgy methods. Calculations and economic evaluations of the production and use of spongy ferrotungsten for alloying special steels are carried out. The developed technological regulations for the production of spongy ferrotungsten allow its use as an alloying material. An assessment of economic efficiency was carried out and the main factors influencing it were determined. To the factors that influence economic efficiency, it should be attributed: the exclusion of the use of precious silicon and aluminum powders as a reducing agent and their replacement with carbon-containing waste; elimination of the operation of dividing molten ingots, which reduces the cost of redistribution of recovery of liquid concentrates. When spongy tungsten is used as an alloying material, the dissolution time of tungsten in the melt is reduced, which reduces losses of tungsten and other alloying elements and deoxidizers and increases the productivity of the main metallurgical units. All these factors reduce the cost of smelting redistribution. The work evaluates the economic efficiency of obtaining spongy ferrotungsten and its use in the smelting of high-speed steel P6M5 in an electric arc furnace DSV-25. When using a new alloying material as an alloying additive in the steel melt, such factors as a decrease in the expenditure coefficients for the redistribution of the melt into tungsten, chromium, molybdenum, and vanadium due to a decrease in the oxidation potential of the steel melt, the specific consumption of technological energy with an increase in the absorption rate of tungsten by the steel melt in 5–7 times compared to standard fused ferrotungsten, etc.